The Integration of Islamic Religious Values in the Ritual Mantras of Pinisi Boat-Making as Instructional Material for Literature Learning in Islamic Schools - Ilham Zulhidayat Bursan; A. Andayani; Raheni Suhita (Bumi Publikasi Nusantara, 2027)
This study aims to integrate Islamic religiosity values embedded in the ritual mantras of Pinisi boat-making into literary learning materials for madrasah education. Employing a mixed-methods approach with an exploratory sequential design, the research began with qualitative data collected through interviews with five pammaca (ritual specialists) and document analysis. This phase was followed by a quantitative survey involving five teachers and ten students in Bulukumba, Indonesia. The findings reveal that Islamic values are reflected in several ritual stages, including annakbang kalabiseang, annattak kalabiesang, apasilli, and ammocci, encompassing dimensions of faith, knowledge, worship, spiritual experience, and practical application. Both teachers and students expressed strong support for integrating these values into literary learning materials, as it enriches instructional content, strengthens character education, and contributes to the preservation of local culture. Furthermore, the study highlights the practical relevance of this integration for curriculum development and culturally responsive teaching strategies.